1985
DOI: 10.1002/art.1780281205
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral inflammatory vascular disease in Sjögren's syndrome. Association with nervous system complications

Abstract: Two histopathologic types of inflammatory vascular disease (IVD) occur in Sjogren's syndrome (SS):mononuclear IVD (MIVD) and neutrophilic IVD (NIVD). We describe 50 SS patients with IVD (30 with NIVD and 20 with MIVD). Thirty-three (66%) of the SS patients with biopsy-documented IVD had nervous system disease unattributable to other causes. Nineteen patients (58%) had involvement of both the central and peripheral nervous systems, while 9 had peripheral and 5 had central nervous system dysfunction alone. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
1
3

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(36 citation statements)
references
References 22 publications
4
28
1
3
Order By: Relevance
“…However, it has been reported that pSS patients may also suffer from visual acuity changes or visual quality disturbances as a result of optic neuropathy, which may occur before or at the same time as the diagnosis of pSS (1)(2)(3) . Thus, when evaluating the visual quality of pSS patients, both functional and morphological analyses of the optic nerve should also be performed in addition to examination of the ocular surface structures.…”
Section: Resultados: O Teste Cs Em Pacientes Pss Não Diferiu Do Que Omentioning
confidence: 99%
“…However, it has been reported that pSS patients may also suffer from visual acuity changes or visual quality disturbances as a result of optic neuropathy, which may occur before or at the same time as the diagnosis of pSS (1)(2)(3) . Thus, when evaluating the visual quality of pSS patients, both functional and morphological analyses of the optic nerve should also be performed in addition to examination of the ocular surface structures.…”
Section: Resultados: O Teste Cs Em Pacientes Pss Não Diferiu Do Que Omentioning
confidence: 99%
“…Furthermore, it is considered a marker of extraglandular involvement since it is associated with lymphadenopathy, splenomegaly and vasculitis [54,55].…”
Section: Clinical Associationsmentioning
confidence: 99%
“…Alexander and coworkers displayed biopsy-proven peripheral vasculitis accompanying CNS complications frequently and necrotizing spinal arteritis at autopsy in a patient, supporting the vasculitic theory [9]. Other studies have demonstrated that a vasculitic cutaneous involvement was frequent in pSS [10][11][12][13]. Other studies by Alexander and colleagues showed that only 1 of 13 patients had stenosis of the internal carotid artery [10].…”
Section: Discussionmentioning
confidence: 78%